Calcium polyphosphate coacervates: effects of thermal treatment - Kopp, Willian; Barud, Hernane S. [UNESP]; Paz, Marcelo F.; Bueno, Luciano A.; Giordano, Raquel L. C.; Ribeiro, Sidney José Lima [UNESP] (Springer, 2012)
The addition of calcium chloride eletrolyte to sodium polyphosphate solutions lead to Calcium polyphosphate coacervates. The effects of a thermal treatment were investigated with the objective to increase the relative stability of the obtained material. Thermogravimetry analysis indicates that coacervates became less hydrophilic and more thermally stable after the thermal treatment. Crystallization was identified through differential scanning calorimetry and X-ray diffraction. Morphological changes were observed after the thermal treatment by scanning electron microscopy. N-2 adsorption-desorption isotherms suggest that both materials, thermally treated or not, display type IV isotherms, low superficial area and mesoporous structure. Stability experiments in solutions at different pH values show that the thermally treated calcium polyphosphate is relatively more stable than the non-treated coacervate.
Keywords: Calcium polyphosphate; Polyeletrolite coacervation; Phosphate gel; Thermal treatment